EFFECT OF INTELLECTUAL CAPITAL INABILITY TRANSFER OF KNOWLEDGE OF MUHAMMADIYAH MAKASSAR UNIVERSITY LECTURER - Aris Pasigai; Nasrullah Nasrullah; Agus Ramadani (Universitas Muhammadiyah Makassar, 2021)
This study aims to assess the impact of intellectual capital on the knowledge transfer ability of lecturers at the Muhammadiyah University of Makassar (Case Study Management Study Program). The type of research used in this research Management Study Program of the Muhammadiyah University of Makassar. The type of data used is primary data with data analysis techniques using a questionnaire, while the techniques used to analyze are: validity, reliability, simple test, hypothesis testing and determination coefficient test. From the results of the research conducted, it can be shown that intellectual capital has a positive and significant effect on the knowledge transfer ability of the arithmetic value 22.531 t table 3.3225 sig 0.000